Management of library networking (Anmol Pubications, 2001)
Contents of material: 1/ Library networking management. 2/ Networking in libraries. 3/ Networking and resource sharing. 4/ Multimedia libraries and its resources. 5/ Automated networking. 6/ Future of libraries.